2024
DOI: 10.1038/s44320-024-00019-8
|View full text |Cite
|
Sign up to set email alerts
|

AI-guided pipeline for protein–protein interaction drug discovery identifies a SARS-CoV-2 inhibitor

Philipp Trepte,
Christopher Secker,
Julien Olivet
et al.

Abstract: Protein–protein interactions (PPIs) offer great opportunities to expand the druggable proteome and therapeutically tackle various diseases, but remain challenging targets for drug discovery. Here, we provide a comprehensive pipeline that combines experimental and computational tools to identify and validate PPI targets and perform early-stage drug discovery. We have developed a machine learning approach that prioritizes interactions by analyzing quantitative data from binary PPI assays or AlphaFold-Multimer pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 100 publications
0
1
0
Order By: Relevance
“…In their study, the authors identified and validated PPIs as targets through experimental and computational tools such as binary PPI assays and yeast two-hybrid screening. The use of AI allowed them to score and prioritise PPIs and to find an inhibitor of NSP10 and NSP16 interaction, which led to the reduction in SARS-CoV-2 replication [ 157 ].…”
Section: Ai and Ddmentioning
confidence: 99%
“…In their study, the authors identified and validated PPIs as targets through experimental and computational tools such as binary PPI assays and yeast two-hybrid screening. The use of AI allowed them to score and prioritise PPIs and to find an inhibitor of NSP10 and NSP16 interaction, which led to the reduction in SARS-CoV-2 replication [ 157 ].…”
Section: Ai and Ddmentioning
confidence: 99%